A Comparison of Energy Expenditure Across 3 Gaming Platforms Using an Activity-Based Dance Game. Issue 4 (October 2016) - Powers, Matthew M.; Henning, Daniel L.; Stafford, Christian P.; Eason, Jane M.
Abstract : Background: Obesity rates have continued to increase and much of this increase is due to physical inactivity. One of the major contributors to physical inactivity is excessive participation in sedentary activities such as playing video games. However, game developers recently have begun developing more active gaming and many of these games are available across a variety of gaming systems. With several platforms available for active video gaming, there is limited research comparing differences in energy expenditure (EE) across the different devices. Objective: The purpose of this study was to compare EE and heart rate (HR) responses while playing an activity-based dance game on the Xbox Kinect, Playstation Move, and Nintendo Wii. Design: This was a repeated-measures study design. Methods: Fifty-one participants played Just Dance 3 on each system for 15 minutes per session in a randomized order. Energy expenditure in kilocalories per minute was estimated using a triaxial accelerometer, and HR in beats per minute was measured with a HR belt monitor. Results: Participants burned significantly more kilocalories on the Kinect compared with the Playstation and the Wii. There was no significant difference in EE between the Playstation and the Wii. As regards average HR, the Kinect resulted in a higher HR compared with the Playstation and the Wii. There was no difference in HR response between the Playstation and Wii. Conclusions: This study demonstrates that the Kinect is the best gaming platform for promoting higher EE and HR when playing an activity-based dance game.